2019
DOI: 10.3389/fchem.2019.00459
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Separation of Antioxidants and Carbohydrates From Food Wastes Using Aqueous Biphasic Systems Formed by Cholinium-Derived Ionic Liquids

Abstract: The food industry produces significant amounts of waste, many of them rich in valuable compounds that could be recovered and reused in the framework of circular economy. The development of sustainable and cost-effective technologies to recover these value added compounds will contribute to a significant decrease of the environmental footprint and economic burden of this industry sector. Accordingly, in this work, aqueous biphasic systems (ABS) composed of cholinium-derived bistriflimide ionic liquids (ILs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
(84 reference statements)
0
12
0
Order By: Relevance
“…Their biocompatible nature is usually ascribed to their similar chemical structure to the water-soluble essential nutrient cholinium chloride (also known as vitamin B4), which is found in food obtained from vegetable or animal sources and supports several biological functions [26,27]. The cholinium cation has been combined with a wide variety of organic or inorganic anions, producing ILs with different properties [28][29][30]. In the field of biomass extractions, Ribeiro et al [31] applied aqueous solutions of cholinium-based ILs as potential alternatives to imidazolium-based counterparts for the extraction of polyphenols and saponins from the leaves and aerial parts of Ilex paraguariensis (mate) and Camellia sinensis (tea).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their biocompatible nature is usually ascribed to their similar chemical structure to the water-soluble essential nutrient cholinium chloride (also known as vitamin B4), which is found in food obtained from vegetable or animal sources and supports several biological functions [26,27]. The cholinium cation has been combined with a wide variety of organic or inorganic anions, producing ILs with different properties [28][29][30]. In the field of biomass extractions, Ribeiro et al [31] applied aqueous solutions of cholinium-based ILs as potential alternatives to imidazolium-based counterparts for the extraction of polyphenols and saponins from the leaves and aerial parts of Ilex paraguariensis (mate) and Camellia sinensis (tea).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that [Ch]Cl was the best solvent option for the extraction of saponins and phenolic compounds, either from mate or tea [31]. Recently, cholinium-based ILs were studied to simultaneously extract and isolate antioxidants and carbohydrates from food waste [29]. Despite all promising achievements, there is still a long path to take advantage of all the potential of more biocompatible ILs as alternative solvents to extract high-value compounds from biomass.…”
Section: Introductionmentioning
confidence: 99%
“…22 It was also shown that some of these ammonium bistriflimide ILs present substantially less toxicity to Caco-2 human cells than some commonly used bistriflimide-based ionic liquids. 23 The functionalization of ILs using either hydroxyl or ether groups in their chemical structure is a well-known strategy in order to tune their properties. However, quantitative analyses in which one compares the changes in properties of these types of replacements (hydroxyl or alkoxy or alkyl, all of them of comparable/similar volumetric sizes) are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous work has shown the importance of adding hydroxyl groups to the ammonium cation, enhancing the hydrogen bonding ability of ILs, to produce room-temperature water-soluble bistriflimide-based ionic liquids . It was also shown that some of these ammonium bistriflimide ILs present substantially less toxicity to Caco-2 human cells than some commonly used bistriflimide-based ionic liquids …”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that aqueous ChCl-Gly is among the most readily biodegradable and is "practically harmless" to the aquatic ecosystem (Juneidi et al, 2015). Additionally, newer generations, i.e., cholinium-derived ILs were chosen as the component of an aqueous two-phase (ATP) to simultaneously extract and recover antioxidants and carbohydrates from food waste (Neves et al, 2019). These used ILs were proven to have low toxicity toward human intestinal epithelial cells (Caco-2 cell line).…”
mentioning
confidence: 99%